ANALISIS DETERMINAN KREDIT PADA BANK PEREKONOMIAN RAKYAT DI KOTA PADANG - Shupia Rani; Alpon Satrianto (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to examine and analyze the influence of Third Party Funds (TPF), Bank Size, Operating Expenses to Operating Revenue (BOPO), Net Interest Margin (NIM), and BI Rate on credit in Rural Credit Banks (BPR) in Padang City. This study uses a quantitative approach with quarterly panel data for the period 2015–2024 obtained from the Financial Services Authority (OJK) and analysis was conducted using panel data regression methods through EViews 12 software. The research results show that TPF, Bank Size, and NIM have a positive and significant effect on credit in BPR in Padang City, while BOPO and BI Rate have a negative but not significant effect on credit in BPR in Padang City. These findings indicate that fund availability, bank capacity, and profit margin (NIM) are the main determinant factors in credit distribution of BPR in Padang City, while the insignificance of BOPO and BI Rate shows that operational efficiency and macroeconomic conditions have not become the main considerations in determining credit volume. Based on these results, it is recommended that BPR management focus on optimizing TPF collection to strengthen funding base, increasing business scale to expand credit distribution capacity, maintaining optimal NIM levels to ensure profitability, anticipating BI Rate changes through appropriate pricing strategy and timing adjustments, and strengthening credit risk management systems.